Methods for studying collective action in rural development - Meinzen-Dick, Ruth S.; Di Gregorio, Monica; McCarthy, Nancy (International Food Policy Research Institute, 2004)
With renewed recognition of the importance of collective action in many aspects of agriculture, natural resource management, and rural development programs in developing countries, there is a need for research on the factors that affect its emergence, as well as its performance. Yet because of its dynamic nature, collective action is difficult to measure and study. This article discusses ways of conceptualizing collective action to provide researchers from various disciplines with a basic framework for understanding and studying collective action. It highlights specific features of collective action that are relevant to identify best practice methodological approaches and research techniques. The main part of the paper then describes how collective action can be operationalized, highlighting the strengths and weaknesses of different methods, as well as discussing complementarities among methods. This discussion provides an overview on the use of qualitative, quantitative, experimental, and action research methods for studying collective action.